A composite catalyst for solution plasma catalysis and its preparation method and application

By modifying the -tetrakis(4-carboxyphenyl)porphine on graphite phase carbon nitride to form a carbon nitride/porphyrin composite catalyst, the problem of non-sustaining discharge of solution plasma catalysts and low accumulation concentration in the prior art is solved, and more efficient and sustainable hydrogen peroxide generation is achieved.

CN119500259BActive Publication Date: 2025-05-09NORTHEAST NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411635390.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-05-09
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

In the in-situ synthesis of H2O2, the existing solution plasma catalysts have problems such as non-sustaining discharge and low accumulation concentration of hydrogen peroxide.

Method used

By non-covalently modifying the medium-tetrakis(4-carboxyphenyl)porphine with graphite phase carbon nitride, a carbon nitride/porphyrin composite catalyst is formed, and the photosensitive unit of the porphyrin and the catalytic activity of the carbon nitride is used to enhance the adsorption and activation ability of oxygen.

Benefits of technology

The solution plasma discharge time was significantly extended to 9 hours, and 32 mM hydrogen peroxide was obtained accumulated, which increased the yield of hydrogen peroxide compared to the single graphite phase carbon nitride catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500259B_ABST
    Figure CN119500259B_ABST
Patent Text Reader

Abstract

The invention discloses a composite catalyst for solution plasma catalysis and its preparation method and application, which belongs to the field of plasma discharge and catalysis technology, wherein the preparation method of the composite catalyst comprises the following steps: melamine is heated to 500-540°C for heat treatment, then cooled to obtain graphite phase carbon nitride; graphite phase carbon nitride and medium-tetra (4-carboxylphenyl) porphine are mixed, and heated to 280-320°C for heat treatment, then cooled to obtain a composite catalyst. The present invention interacts with graphite phase carbon nitride through π-π stacking by non-covalent modification of medium-tetra (4-carboxylphenyl) porphine to form a stable composite system; the composite catalyst can significantly improve the adsorption and activation ability of oxygen, prolong the solution plasma discharge time, and can greatly improve the yield of hydrogen peroxide compared to a single graphite phase carbon nitride catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plasma discharge and catalysis, in particular to a composite catalyst for solution plasma catalysis and a preparation method and application thereof. Background Art

[0002] Solution plasma catalysis in H 2 O and O 2 Implement H 2 O 2 The technology has great potential for in-situ sustainable synthesis of H. 2 O 2 , and has the advantage of fast reaction rate. In previous work (PNAS, 2024, 121, e2410504121), carbon nitride (C 3 N 4 ) can promote the solution plasma catalytic synthesis of H 2 O 2 However, a single C 3 N 4 The system is still limited by the discontinuity of discharge and the accumulation of hydrogen peroxide concentration. Usually, the discharge can only last about 1 hour, and the hydrogen peroxide concentration can only accumulate to about 2 mmol per liter.

[0003] The combination of catalyst and photosensitizer is to increase the 2 The activation of porphyrin is an effective strategy for preparing hydrogen peroxide. The energy transfer effect between the photosensitizer and the catalyst in the complex can improve its ability to produce singlet oxygen. Porphyrin is a highly conjugated system, and the high degree of π electron delocalization provides a good pathway for electron transfer and energy transfer between covalent organic frameworks. At the same time, porphyrin has excellent light absorption ability and exhibits high absorption coefficients in the visible and near-infrared regions, which means that it can more efficiently utilize photons and electrons in solution plasma.

[0004] Currently, porphyrins are used to 3 N 4 There have been many reports on the covalent / non-covalent modification of 3 N 4 The surface functionalization is carried out by chemical bonding, while non-covalent functionalization includes π-π stacking interaction and electrostatic interaction. However, most of the current studies only use porphyrin to modify C 3 N 4 To expand its light response range and promote surface electron transfer, and in terms of catalysis, hydrogen peroxide is prepared by photocatalysis, while the carbon nitride / porphyrin composite system suitable for solution plasma catalysis is still in research gaps. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a composite catalyst for solution plasma catalysis to solve the problems raised in the above background technology.

[0006] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0007] A method for preparing a composite catalyst for solution plasma catalysis comprises the following steps:

[0008] The melamine is heated to 500-540° C. for heat treatment, and then cooled to obtain graphite phase carbon nitride;

[0009] The graphite phase carbon nitride and meso-tetrakis (4-carboxyphenyl) porphine are mixed, heated to 280-320° C. for heat treatment, and then cooled to obtain a composite catalyst.

[0010] Preferably, the step of heating melamine to 500-540° C. for heat treatment specifically comprises:

[0011] The melamine is placed in air and heated to 500-540°C at a heating rate of 3-7°C / min for heat treatment.

[0012] Preferably, the step of mixing graphite phase carbon nitride and meso-tetrakis(4-carboxyphenyl)porphine and heating to 280-320° C. for heat treatment specifically comprises:

[0013] The graphite phase carbon nitride and meso-tetrakis (4-carboxyphenyl) porphine are mixed and ground, and then the obtained powder is placed in a protective atmosphere and heated to 280-320° C. at a heating rate of 3-7° C. / min for heat treatment.

[0014] Preferably, the protective atmosphere is a nitrogen atmosphere.

[0015] Preferably, the mass ratio of the graphite phase carbon nitride to meso-tetrakis(4-carboxyphenyl)porphine is 200:(5-50).

[0016] Another object of an embodiment of the present invention is to provide a composite catalyst for solution plasma catalysis prepared by the above preparation method.

[0017] Another object of an embodiment of the present invention is to provide an application of the above-mentioned composite catalyst in preparing hydrogen peroxide by solution plasma.

[0018] The present invention composites meso-tetra(4-carboxyphenyl)porphine with graphite-phase carbon nitride through non-covalent modification to form a carbon nitride / porphyrin composite catalyst; meso-tetra(4-carboxyphenyl)porphine interacts with graphite-phase carbon nitride through π-π stacking to form a stable composite system; the composite catalyst can significantly improve the adsorption and activation capabilities of oxygen, extend the solution plasma discharge time to 9 hours, and accumulate 32mM hydrogen peroxide, which greatly improves the yield of hydrogen peroxide (from 2mM to 32mM) compared with a single graphite-phase carbon nitride catalyst; this achievement overcomes the bottleneck problems of discontinuous discharge and low accumulated concentration of hydrogen peroxide in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the structure of a carbon nitride / porphyrin composite catalyst prepared in an embodiment of the present invention;

[0020] Figure 2 TEM images of the carbon nitride / porphyrin composite catalyst and TCPP prepared in the embodiment of the present invention; in the figure, a is a TEM image of TCPP; b is a TEM image of the carbon nitride / porphyrin composite catalyst prepared in Example 1 of the present invention; c is a TEM image of the carbon nitride / porphyrin composite catalyst prepared in Example 2 of the present invention; d is a TEM image of the carbon nitride / porphyrin composite catalyst prepared in Example 3 of the present invention;

[0021] Figure 3 1 is a diagram showing the discharge experiment results of the carbon nitride / porphyrin composite catalyst prepared in an embodiment of the present invention in a solution plasma; in the figure, a is a schematic diagram of the discharge experiment of the carbon nitride / porphyrin composite catalyst in a solution plasma; b is the H of different materials during the discharge process 2 O 2 The concentration changes with time; c is the H concentration of graphite phase carbon nitride and carbon nitride / porphyrin composite catalyst during long-term discharge. 2 O 2 Graph of concentration changes over time. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In the prior art, although the carbon nitride catalyst can improve the catalytic activity in the process of preparing hydrogen peroxide by solution plasma catalysis, its discharge time and cumulative concentration of hydrogen peroxide are low. This problem mainly stems from the limited improvement of the oxygen adsorption and activation ability of carbon nitride. Therefore, the prior art solution has obvious defects in improving the plasma catalytic efficiency. In order to overcome the defects of the prior art solution, the embodiment of the present invention proposes a new technical method, namely, developing a carbon nitride / porphyrin composite material system. The problems in the prior art are solved by the following aspects:

[0024] 1. Carbon nitride / porphyrin composite: The photosensitive unit of porphyrin can capture the light of the solution plasma channel, activate molecular oxygen through the singlet oxygen pathway, further enhance the activation ability of molecular oxygen, and prolong the discharge time.

[0025] 2. Improved catalytic performance: The combination of carbon nitride and porphyrin units not only improves the surface electronic structure of carbon nitride, but also enhances its adsorption and activation of oxygen, while simultaneously extending the discharge time and increasing the concentration of hydrogen peroxide, thereby improving the reaction efficiency in the plasma catalytic process. Compared with single carbon nitride, the composite system can promote the generation of hydrogen peroxide for a longer period of time.

[0026] Specifically, in the embodiment of the present invention, graphite phase carbon nitride (CCN, gC 3 N 4 ) modified with photosensitizer to increase O 2 Activation-promoted solution plasma synthesis of H 2 O 2 It is an effective method. The photosensitizer has a wide absorption range. The singlet excited state molecules formed after being excited are more likely to generate triplet intermediates through the ISC process, and the lifetime of the triplet intermediates is long enough to induce O 2 Convert to 1 O 2 In addition, the tetrakis(4-carboxyphenyl)porphine (TCPP, C 44 H 26 N 4 O 8 ) is a photosensitizer based on porphyrin units. Carbon nitride was non-covalently modified with TCPP, and the carbon nitride / porphyrin complex was prepared by solid chemical method. The photo- / electrically induced energy transfer effect between TCPP and carbon nitride reached 6000 μmol·L in solution plasma catalysis. -1 ·h -1 H 2 O 2 The generation rate was increased by 2.5 % and the discharge time of the plasma was extended to 9 h, accumulating 32 mM H 2 O 2The specific implementation scheme can refer to the following examples, but is not limited thereto.

[0027] Example 1: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0028] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 520° C. at a heating rate of 5° C. / min in air for heat treatment, and then cooled to room temperature to obtain a yellow product, which was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside;

[0029] S2, 200 mg of the above-mentioned graphite phase carbon nitride and 5 mg of meso-tetrakis (4-carboxyphenyl) porphine (TCPP) were mixed and ground for 30 min, and then the obtained powder was placed in a crucible with a lid, and placed in a nitrogen atmosphere, heated to 300 ° C at a heating rate of 5 ° C / min for heat treatment, maintained for 4 hours, and then cooled to room temperature. The obtained dark purple powder is a carbon nitride / porphyrin composite catalyst (denoted as CCN / TCPP-1), and its structural formula is as follows: Figure 1 shown.

[0030] The porphyrin molecule with two-dimensional 18π electron conjugated system adopted in the implementation of the present invention can interact with CCN through π-π stacking. At the same time, the functional group -COOH on the periphery of the TCPP ring may undergo carboxylation reaction with the amino group on the edge of CCN, resulting in the TCPP molecule being covalently bound together with CCN through amide bonds. Therefore, both non-covalent and covalent interactions may form CCN / TCPP polymers. However, due to the small number of amino groups on the edge of CCN, the covalent interaction between TCPP and CCN molecules may be very small. Therefore, the hybridization effect between TCPP and CCN molecules mainly comes from non-covalent interactions. The greatest advantage of non-covalent interaction is that it can maintain the physical properties of TCPP and CCN respectively.

[0031] Example 2: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0032] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 520° C. at a heating rate of 5° C. / min in air for heat treatment, and then cooled to room temperature to obtain a yellow product, which was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside;

[0033] S2. Mix 200 mg of the above-mentioned graphite phase carbon nitride and 20 mg of medium-tetrakis(4-carboxyphenyl)porphine (TCPP) and grind for 30 min. Then put the resulting powder into a crucible with a lid, place it in a nitrogen atmosphere, heat it to 300 ° C at a heating rate of 5 ° C / min for heat treatment, keep it for 4 h, and then cool it to room temperature to obtain a dark purple powder, which is a carbon nitride / porphyrin composite catalyst (recorded as CCN / TCPP-2).

[0034] Example 3: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0035] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 520° C. at a heating rate of 5° C. / min in air for heat treatment, and then cooled to room temperature to obtain a yellow product, which was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside;

[0036] S2. Mix 200 mg of the above-mentioned graphite phase carbon nitride and 50 mg of medium-tetrakis(4-carboxyphenyl)porphine (TCPP) and grind for 30 min. Then put the resulting powder into a crucible with a lid, place it in a nitrogen atmosphere, heat it to 300 ° C at a heating rate of 5 ° C / min for heat treatment, keep it for 4 h, and then cool it to room temperature to obtain a dark purple powder, which is a carbon nitride / porphyrin composite catalyst (recorded as CCN / TCPP-3).

[0037] Example 4: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0038] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 500° C. at a heating rate of 3° C. / min in air for heat treatment, and maintained for 4 h. The product was then cooled to room temperature to obtain a yellow product, which was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside.

[0039] S2. Mix 200 mg of the above-mentioned graphite phase carbon nitride and 10 mg of medium-tetrakis(4-carboxyphenyl)porphine (TCPP) and grind for 30 min. Then put the resulting powder into a crucible with a lid, place it in a nitrogen atmosphere, heat it to 280 ° C at a heating rate of 3 ° C / min for heat treatment, keep it for 4 h, and then cool it to room temperature to obtain a dark purple powder, which is the carbon nitride / porphyrin composite catalyst.

[0040] Example 5: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0041] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 540° C. at a heating rate of 7° C. / min in air for heat treatment, and then cooled to room temperature to obtain a yellow product, which was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside;

[0042] S2. Mix 200 mg of the above-mentioned graphite phase carbon nitride and 40 mg of meso-tetrakis(4-carboxyphenyl)porphine (TCPP) and grind for 30 min. Then put the obtained powder into a crucible with a lid, and place it in a nitrogen atmosphere. Heat it to 320°C at a heating rate of 7°C / min for heat treatment, keep it for 4 h, and then cool it to room temperature to obtain a dark purple powder, which is the carbon nitride / porphyrin composite catalyst.

[0043] Example 6: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0044] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 510° C. at a heating rate of 4° C. / min in air for heat treatment, and then cooled to room temperature to obtain a yellow product, which was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside;

[0045] S2. Mix 200 mg of the above-mentioned graphite phase carbon nitride and 25 mg of meso-tetrakis(4-carboxyphenyl)porphine (TCPP) and grind for 30 min. Then put the obtained powder into a crucible with a lid, and place it in a nitrogen atmosphere. Heat it to 390°C at a heating rate of 4°C / min for heat treatment, keep it for 4 h, and then cool it to room temperature to obtain a dark purple powder, which is the carbon nitride / porphyrin composite catalyst.

[0046] Example 7: This example provides a method for preparing a composite catalyst for solution plasma catalysis, which comprises the following steps:

[0047] S1. 6 g of melamine was placed in a crucible with a lid, and heated to 530° C. at a heating rate of 6° C. / min in air for heat treatment, and maintained for 4 h. Then, a yellow product was obtained after cooling to room temperature, and the product was collected and ground into fine powder to obtain graphite phase carbon nitride (CNN), which was set aside.

[0048] S2. Mix 200 mg of the above-mentioned graphite phase carbon nitride and 35 mg of meso-tetrakis(4-carboxyphenyl)porphine (TCPP) and grind for 30 min. Then put the obtained powder into a crucible with a lid, and place it in a nitrogen atmosphere. Heat it to 310°C at a heating rate of 6°C / min for heat treatment, keep it for 4 h, and then cool it to room temperature to obtain a dark purple powder, which is the carbon nitride / porphyrin composite catalyst.

[0049] Performance test: 1. The carbon nitride / porphyrin composite catalysts CCN / TCPP-1, CCN / TCPP-2, CCN / TCPP-3 and TCPP alone prepared in Examples 1-3 were observed by TEM. The results are as follows: Figure 2 As shown in ad; it can be seen from the figure that CCN / TCPP-1, CCN / TCPP-2, CCN / TCPP-3 and TCPP alone are all irregular nanosheet morphologies, and their average size is about 100×300nm. TCPP and CCN have similar sizes, which makes TCPP better dispersed and attached to CCN nanosheets.

[0050] Second, the carbon nitride / porphyrin composite catalysts CCN / TCPP-1, CCN / TCPP-2, CCN / TCPP-3 prepared in Examples 1-3 and CCN, TCPP, and water were used to carry out solution plasma catalytic H 2 O 2 The generated experiment. Figure 3 As shown, Figure 3 A photo of the discharge of CCN / TCPP-2 suspension is shown in Figure a. Specifically, the plasma reactor device includes a pulse power supply, a double-layer beaker and two tungsten electrodes (one is a solid cylinder and the other is a hollow tube). 2 O 2 It is in H 2 O and O 2 Saturated H 2 O was prepared, and the discharge system was kept at a constant temperature (10°C) by external condensed water. 30 mg of the catalyst was placed in a sandwich beaker containing 100 mL of deionized water and ultrasonically dispersed to obtain a uniformly dispersed suspension. Then, O 2 After 30 min of continuous flow of the solution, the catalyst surface reached 0 2 Finally, the pulse power supply is turned on to generate plasma in the area between the two electrodes. Figure 3 As shown in b, in the systems of CCN, TCPP and CCN / TCPP-x (x = 1, 2, 3), H 2 O 2 The concentration of H increases gradually with time. After 1 h of discharge, the H concentrations of CCN, TCPP, CCN / TCPP-1, CCN / TCPP-2 and CCN / TCPP-3 2 O 2 The concentrations can reach 5.02mM, 2.85mM, 5.21mM, 5.9mM and 5.4mM respectively. Among them, the catalytic activity of CCN / TCPP-x is significantly higher than that of CCN and TCPP alone, indicating that their combination enhances the H 2O 2 In addition, a long-term discharge test was conducted using CCN / TCPP-2, which has the highest catalytic activity. Figure 3 As shown in c, the results show that CCN / TCPP-2 can not only improve H 2 O 2 The activity of H 2 O 2 The concentration of 20mM was increased to 32mM. In conclusion, the above test results prove that the composite catalyst prepared in the embodiment of the present invention is effective in the solution plasma catalytic synthesis of H 2 O 2 It has the advantages of high efficiency and sustainability.

[0051] According to the above tests, the role of carbon nitride / porphyrin composite catalyst in solution plasma is as follows: the high π electron delocalization of meso-tetra(4-carboxyphenyl)porphine (TCPP) can enhance the light absorption ability of the catalyst, especially in the visible and near-infrared regions, showing a high absorption coefficient. In the solution plasma environment, TCPP can effectively capture photons in the solution plasma channel and promote O 2 The photosensitization effect significantly improves the activation efficiency of molecular oxygen, making the plasma catalytic reaction more efficient. Compared with the single carbon nitride system, the O 2 The activation ability is significantly enhanced, thereby improving H 2 O 2 The generation rate reached 6000 μmol·L -1 ·h -1 This effect greatly improves the reaction rate and yield, overcoming the limitation of low light utilization efficiency of traditional catalysts in solution plasma environment.

[0052] The optimization effect of TCPP on the surface electronic structure of carbon nitride is as follows: through the compound with TCPP, the surface electronic structure of carbon nitride is optimized, and the surface electron transfer rate and interface charge separation efficiency are significantly improved. 3 N 4 The non-covalent interaction between the two promotes the transfer of interfacial electrons, reduces the recombination of photogenerated electrons and holes, and improves the overall activity of the catalyst. This optimization of the electronic structure not only enhances the adsorption of oxygen molecules, but also significantly improves its activation ability, prolongs the discharge time in the catalytic reaction, and improves the overall efficiency of the plasma catalytic process. This optimization solves the problem of traditional gC 3 N 4The catalyst has defects in discharge sustainability and oxygen activation ability, especially in maintaining high activity during long-term discharge.

[0053] In addition, the carbon nitride / porphyrin composite catalyst is prepared under controllable conditions, specifically, by using a solid chemical method, by precisely controlling gC 3 N 4 With the composite ratio of TCPP, and the heat treatment process under nitrogen protection, the carbon nitride / porphyrin composite catalyst of different TCPP loadings can be prepared. By controlling the heat treatment temperature and time of the composite material, it is ensured that the composite material has a stable structure and excellent catalytic activity. This controllable preparation process can ensure the structural homogeneity and performance consistency of the catalyst, so that the composite catalyst of different loadings all shows excellent catalytic performance under different plasma discharge conditions. Compared with the prior art, the preparation method provided by the embodiment of the present invention is more refined and controllable, ensures the high efficiency and stability of the catalyst, and is suitable for large-scale production.

[0054] The composite catalyst prepared in the embodiment of the present invention not only enhances the short-term catalytic performance by improving the light absorption and electron transfer capabilities, but also pays special attention to the stability of the catalyst in long-term reactions. Through non-covalent modification, the damage to the catalyst structure that may be caused by covalent modification is avoided, ensuring its catalytic activity in long-term discharge reactions. The composite catalyst remains stable during a discharge time of up to 9 hours and continuously generates hydrogen peroxide, greatly extending the discharge time and the service life of the catalyst. Compared with traditional catalysts, the composite catalyst prepared in the embodiment of the present invention is more effective in preparing H in solution plasma catalysis. 2 O 2 The catalytic activity is longer and more stable during the process, which is suitable for long-term operation in practical applications.

[0055] In summary, the embodiments of the present invention significantly improve the generation efficiency of hydrogen peroxide, prolong the solution plasma discharge time, optimize the electronic structure of the catalyst, break through many limitations of the prior art, and have great significance for the environmentally friendly and efficient preparation of H 2 O 2 It has broad application prospects.

[0056] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. Use of a composite catalyst for solution plasma catalysis in preparing hydrogen peroxide by solution plasma, characterized in that: The preparation method of the composite catalyst comprises the following steps: The melamine is heated to 500-540° C. for heat treatment, and then cooled to obtain graphite phase carbon nitride; The graphite phase carbon nitride and meso-tetrakis(4-carboxyphenyl)porphine are mixed, heated to 280-320° C. for heat treatment, and then cooled to obtain a composite catalyst; The step of heating melamine to 500-540° C. for heat treatment specifically comprises: The melamine is placed in air and heated to 500-540°C at a heating rate of 3-7°C / min for heat treatment; The step of mixing graphite phase carbon nitride and meso-tetrakis(4-carboxyphenyl)porphine and heating to 280-320° C. for heat treatment specifically comprises: The graphite phase carbon nitride and meso-tetrakis(4-carboxyphenyl)porphine are mixed and ground, and then the obtained powder is placed in a protective atmosphere and heated to 280-320° C. at a heating rate of 3-7° C. / min for heat treatment; The mass ratio of the graphite phase carbon nitride to meso-tetrakis(4-carboxyphenyl)porphine is 200:(5-50).

2. The use according to claim 1, characterized in that: The protective atmosphere is a nitrogen atmosphere.

Citation Information

Patent Citations

  • Graphite phase-like carbon nitride / tetracarboxylphenylporphyrin nano-composite material and preparation method therefor

    CN105597820A

  • Porphyrin sensitization carbon nitride photocatalyst for producing hydrogen peroxide and preparation method of photocatalyst

    CN110102342A